(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Protein function depends greatly on its structure. Based on this principle, it is vital to study the protein structure in order to understand its function. This study attempts to build the predicted model of lipase gene in Rhodococcus sp. NAM81 using homology modelling method. The predicted structure was then used to investigate the function of protein through several bioinformatic tools. The DNA sequence of lipase gene was obtained from the Rhodococcus sp. NAM81 genome scaffold. Blastx analysis showed 100% identity to the target enzyme andthe appropriate template for homology modelling was determined using Blastp analysis. The 3D protein structure was built using two homology modelling software, EsyPred3D and Swiss Model Server. Both structures built obtained LGScore of greater than 4, which means they are extremely good models according to ProQ validation criteria. Both structures also satisfied the Ramachandran plot structure validation analysis. The predicted structures were 100% matched with each other when superimposed with DaliLite pairwise. This shows that both structure validation servers agreed on the same model. Structure analysis using ProFunc had found seven motifs and active sites that indicate similar function of this protein with other known proteins. Thus, this study has successfully produced a good 3D protein structure for the target enzyme.